Technology, Content, Form And Methods Of Independent Work Of Students In Modern Conditions - Zukhra Ismailova, Olim Turakulov, Shakhnoz Samieva, Igamberdi Tufliev, Abdakim Mamataliev (International Journal of Advanced Science and Technology, 2020)
The article discusses the problem of organizing independent work under the guidance of a teacher, which can be considered effective only if the educational process is organized as a holistic system in each classroom and in extracurricular activities of students. However, these types of work can be partially interconnected with each other, and several types of classroom training on credit training technology have different goals, each of which has its own goal and is an ideal opportunity to perform the above training tasks. The work of independent students under the guidance of a teacher focuses on classroom activities. At the same time, the analysis of normative documents and scientific and methodological literature, the description are presented in the same sense in different sources, but nevertheless the main aspects of this concept are defined, and is a joint training of students and teachers. Type of activity (type of training), which is one of the aspects of ensuring the individual work of the student based on the installation, configuration and control of the teacher.